The impact of smoking on sleep and quality of life: a comprehensive review - Pavan Kumar C. Muddanna; M. Kumaraswamy (International Journal of Research in Medical Sciences, 2024)
Smoking is so widespread and can have such detrimental effects on health that research on the effects of smoking on sleep quality and general quality of life in smokers and non-smokers has already attracted a lot of attention. Numerous research articles have examined the relationship between smoking and sleep, contrasting smokers and non-smokers in various demographic settings and examining the possible impacts of smoking on sleep habits and general quality of life. Data from the corpus of research on the topic is gathered for this review, including differences in the quality of sleep between smokers and non-smokers. Studies comparing smokers’ and non-smokers’ sleep quality frequently find differences in a variety of areas pertaining to sleep patterns and overall sleep health. An overview of this field’s research may be seen below: Smokers often experience poorer sleep compared to non-smokers, with difficulties falling and staying asleep, shorter sleep durations, altered sleep architecture, an increased risk of sleep disorders, and impaired day-to-day functioning. These findings demonstrate how important it is to support smokers in quitting in order to improve their overall health and sleep quality. The summary of the review concluded that smoking can affect the overall quality of life and sleep of both smokers and non-smokers.